Case Report: Carotid cavernous fistula presenting as red eye: case illustration and comprehensive review - Xu, Qi-Bin; Sheng, Wen-Yan (Frontiers in Medicine, 2025)
Carotid cavernous fistula (CCF) is a pathological condition where an abnormal connection forms between the carotid artery and the cavernous sinus. This condition can lead to a variety of ocular and neurological symptoms, often making it difficult to diagnose, especially when patients present with common ocular complaints such as red eye, which is often misdiagnosed as conjunctivitis. The subtle and diverse symptoms of CCF can lead to misdiagnosis, delaying appropriate treatment. This article reports a case of CCF that initially presented with red eye and proptosis, leading to an ophthalmology referral. By comparing pre- and postoperative ocular photographs, the article provides a detailed review of the ophthalmic features, classification, diagnostic methods, and treatment options for CCF. The aim is to enhance clinicians’ understanding of this condition, improve diagnostic accuracy at initial presentation, and promote timely and effective treatment.